A mechanical engineer cannot open his fist - myotonia congenita - Rao, Bhavana Nagabhushana; Bhavana, Raman (International Journal of Research in Medical Sciences, 2017)
Myotonia congenita is a rare congenital neurological disorder, not encountered by many physicians in their clinical practice. Two types are described Thomsen and Becker. The former autosomal dominant, presents at early age and less aggressive as in our patient. Backer is autosomal recessive more aggressive and with muscle weakness. In these disorders group of skeletal muscles contract longer and slow to relax due to mutation in CLCN1 gene leading to chloride channelopathy. They present with difficulty to initiate an action but can do it normally after repeated attempts. Hand and facial muscles are involved in Thomsen disease; they are not weak or atrophic but might have cramps. Diagnosis of Myotonia congenita is clinical and confirmed by electromyography. Many other clinical conditions have myotonia, dystrophic and non-dystrophic. Physiotherapy and membrane stabilizing drugs like anti-epileptics are of choice but with varying success. Genetic counseling is an important part of management of these cases.